Influence of season and planting date on sheath rot incidence in rice - and A.G.R. REDDY, M.M. REDDY, C.S. REDDY (Indian Phytopathology, 2002)
Field trials were conducted at Rajendranagar, Hyderabad, Andhra Pradesh, India, in 1993-94 to assess the effects of season (kharif and rabi) and planting date (12 and 10 dates at 15-day intervals from 1 July and 16 December, respectively) on the incidence of sheath rot in 50 rice cultivars planted in uninoculated plots and plots inoculated with Sarocladium oryzae. Results indicated that for all 4 seasons and all planting dates, the disease index for inoculated treatments was higher than for uninoculated treatments. The disease index was higher in kharif than in rabi crops. For kharif plantings, the disease index was highest for the last planting, but planting date during rabi did not affect the disease index.